From personal wellbeing to relationships : A systematic review on the impact of mindfulness interventions and practices on leaders - Urrila, Laura Ilona (Elsevier, 2021)
This study provides a systematic review of prior empirical research on the impact of mindfulness interventions and practices on leaders. The aim is to integrate existing knowledge and identify future research needs. Mindfulness as a leader-specific practice is defined and discussed to provide conceptual clarity and to highlight the importance of understanding the phenomenon and its value in the context of leadership and individual leader development. A conceptual framework is presented which synthesizes findings from prior works and shows that leaders' mindfulness practices affect various developmental outcomes viewed as important for leaders and leadership. A comprehensive future research agenda for theoretical and empirical advancement is proposed that recommends looking beyond the essential wellbeing and work productivity outcomes and exploring the transformative outcomes of mindfulness interventions and practices related to leaders' relationships and inner growth that involve enhanced self-awareness and social/contextual awareness.
Keywords: Leadership; Leadership development; Leader development; Mindfulness intervention; Mindfulness practice; Mindfulness training; mindfulness; fi=Henkilöstöjohtaminen|en=Human Resource Management|